Comparison of sex determination mechanism of germ cells between birds and fish: Cloning and expression analyses of chicken forkhead box L3‐like gene - Ichikawa, Kennosuke (Dev Dyn, 2019)
BACKGROUND: Birds harbor specific sex determination and differentiation mechanisms. Although the molecular mechanisms associated with sex determination in somatic cells have been elucidated, those for germ cells remain unclear. RESULTS: Here, we characterized the chicken forkhead box L3 (foxl3)‐like gene as a sex‐determination factor in sexually indifferent medaka germline stem cells. The foxl3‐like gene was cloned by rapid amplification of cDNA ends, and the nucleotide sequence was analyzed. The deduced amino acid sequence was compared with FOXL3 sequences from other species, revealing low identity and similarity scores. Expression analysis of foxl3‐like mRNA during gonadogenesis showed female left‐gonad‐specific temporal expression in an egg incubated from 10 to 16 days, as well as low general expression in certain hatched female chicken organs. Moreover, the amino acid sequence deduced for the FOXL3‐like protein displayed low identity with medaka FOXL3, with the FOXL3‐like protein specifically localized in the oogonia, whereas medaka FOXL3 was found in sexually indifferent germline stem cells. Furthermore, the timing of expression differed between the foxl3‐like gene and that of medaka foxl3. CONCLUSIONS: These results suggest that chicken FOXL3‐like protein and medaka FOXL3 differ in terms of their functions as female sex‐determination factors.